Identity and Racial Harassment - Deborah A. Cobb-Clark; Heather Antecol (Institute for the Study of Labor (IZA), 2004)
In a 1996 survey of U.S. military personnel, more than 65 percent experienced racially offensive behavior, and approximately one-in-ten reported threatening incidents or careerrelated racial discrimination. Perceived racial harassment is driven by social classifications that extend beyond racial group membership. While race clearly matters, there is also diversity in the harassment experiences of individuals of the same race with diverging organizational, cultural or social experiences. Social prescriptions constraining inter-racial interactions are associated with higher rates of offensive racial encounters and more careerrelated discrimination, while aspects of an installation?s institutional culture also directly affect harassment. Together, these results lend support for a model of racial harassment that encompasses both institutional factors and a multifaceted notion of racial identity.
Keywords: J81; J70; J15; 330; harassment; identity; U.S. military; Ethnische Diskriminierung; Soziale Beziehungen; Militär; Vereinigte Staaten